Electrochemical degradation of the herbicide picloram using a filter-press flow reactor with a boron-doped diamond or β-PbO2 anode. (10th October 2015) - Pereira, Gabriel F.; Rocha-Filho, Romeu C.; Bocchi, Nerilso; Biaggio, Sonia R.
Abstract: Galvanostatic electrolyses are performed in a filter-press reactor to investigate the electrochemical degradation of picloram (100 mg L −1, from a commercial herbicide formulation) using a boron-doped diamond (BDD) or β-PbO2 anode. The effect of pH (3, 6, or 10), applied current density ( j apl  = 10, 30, or 50 mA cm −2 ), and absence or presence of Cl – ions (25 mM) in the supporting electrolyte (aqueous 0.10 M Na2 SO4 ) is investigated, while the picloram concentration, solution chemical oxygen demand ( COD ) and total organic carbon content ( TOC ), and energy consumption are monitored as a function of electrolysis time. From the obtained results, it is clear that the electrochemical degradation of picloram is possible using either of the anodes, but with different overall performances. In general, the presence of Cl – ions in the supporting electrolyte (leading to electrogenerated active chlorine) has a positive effect on the performance of both anodes, except for TOC abatement using the BDD anode; the best electrodegradation performances are attained at pH values around 6, when HClO is the predominant active-chlorine species. Faster rates of initial electrodegradation of picloram and of solution TOC abatement are obtained as j apl is increased, but, as expected, lower energy consumptions are always attained at the lowest value of j apl . The performances of the two anodes are virtually the same in the initial degradation of picloram; however, the BDD anode greatly surpasses the β-PbO2 anode in the abatement of solution COD or TOC . This confirms the importance of the oxidation power of the anode, even when indirect oxidation by active chlorine plays a concomitant role.